2003
DOI: 10.1007/s00411-003-0177-8
|View full text |Cite
|
Sign up to set email alerts
|

Induction of micronuclei in human fibroblasts and keratinocytes by 25 kV x-rays

Abstract: A relative biological effectiveness (RBE) not much larger than unity is usually assumed for soft x-rays (up to approximately 50 keV) that are applied in diagnostic radiology such as mammography, in conventional radiotherapy and in novel radiotherapy approaches such as x-ray phototherapy. On the other hand, there have been recent claims of an RBE of more than 3 for mammography and respective conventional x-rays. Detailed data on the RBE of soft x-rays, however, are scarce. The aim of the present study was to de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(11 citation statements)
references
References 24 publications
1
10
0
Order By: Relevance
“…Comparison of the means of MN induction for fibroblasts and keratinocytes obtained after irradiation has shown keratinocytes to be at least twice as resistant as fibroblasts (Table 3). In the previous work (13), greater MN induction in human fibroblasts than in keratinocytes was found after X irradiation. Similarly, in cell survival studies, Geara et al (21) and D'Errico et al (22) found keratinocytes to be more radioresistant (higher surviving fraction) than fibroblasts after irradiation.…”
Section: Ir Fitmentioning
confidence: 75%
See 1 more Smart Citation
“…Comparison of the means of MN induction for fibroblasts and keratinocytes obtained after irradiation has shown keratinocytes to be at least twice as resistant as fibroblasts (Table 3). In the previous work (13), greater MN induction in human fibroblasts than in keratinocytes was found after X irradiation. Similarly, in cell survival studies, Geara et al (21) and D'Errico et al (22) found keratinocytes to be more radioresistant (higher surviving fraction) than fibroblasts after irradiation.…”
Section: Ir Fitmentioning
confidence: 75%
“…The MN assay has been described in detail (12,13). In brief, earlypassage cells (third-passage fibroblasts and second-passage keratinocytes) in exponential growth were seeded (at a density of 5 ϫ 10 4 /dish) onto 35-mm petri dishes (Nunc) with 2 ml medium as above, with two dishes per dose.…”
Section: Micronucleus Assaymentioning
confidence: 99%
“…To date, no extensive study has compared two beams of X-rays with high and low energy at the same dose rate or has combined a wide range of biological outputs. Only few studies have reported a higher RBE for X-rays compared to the reference beam (200–250 kV) 1215 . Nevertheless, these studies were performed on very low energy X-rays (below 50 kV) and not necessarily at the same dose rate than the reference X-rays beam.…”
Section: Discussionmentioning
confidence: 99%
“…1C). Interestingly, it is now known that exposure to very low-energy X-rays (25–30 kV) leads to high levels of DNA damage 12 or micronuclei 15 . But, surprisingly, our two beams are within the range of energy from 0.1 to 3 MeV for which an RBE of 1 is classically ascribed 1 .…”
Section: Discussionmentioning
confidence: 99%
“…Most of the observations reported in the literature concern mis-repair of DNA doublestrand breaks, including those of Mestres et al who showed an increase in chromosome aberrations in lymphocytes irradiated with 30 kV, 80 kV and 120 kV X-rays. Slonina et al showed induction of micronuclei with human fibroblasts and keratinocytes irradiated with 25 kV and Lehnert et al with human mammary epithelial cells irradiated with 25 kV and 10 kV X-rays (Slonina et al 2003;Lehnert et al 2006;Mestres et al 2008;Lehnert et al 2008). In addition, some studies have focused on clonogenic survival, including a study by Panteleeva et al, who showed a decrease in clonogenic survival with primary human epidermal keratinocytes and fibroblasts irradiated with 25 kV compared to 200 kV (Panteleeva et al 2003).…”
Section: Introductionmentioning
confidence: 99%